Revitalization of the Walet Park in Sukun Village, Malang as a TOGA Tourist Attraction - Zubair, Anis; Ramadhan, Viry Puspaning; Hidayati, Rahmatina; Hasugian, Elsa Dame Ripka; Savsavubun, Valentinus (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This community service project aims to revitalize Walet Park by improving its cleanliness and using it for planting TOGA (Family Medicinal Plants), addressing cleanliness issues and vacant land in the park. Method: The project involved cleaning the park and planting TOGA in selected areas, with volunteers participating in both activities to enhance the park’s ecological value. Practical Applications: The revitalization transformed Walet Park into a domestic tourist attraction, promoting local tourism and educating the community about the benefits of medicinal plants. Conclusion: Walet Park's transformation into a tourist site highlights the impact of community projects in improving public spaces and addressing local environmental concerns.